SOSIALISME ISLAM: PERSPEKTIF PEMIKIRAN POLITIK H.O.S. TJOKROAMINOTO - Manan, Firman (JWP (Jurnal Wacana Politik), 2016)
In several literatures of Indonesian political thought, the ideas of socialism has been claimed as theÂ doctrine came from and influenced by western political thought. On the other side, Islam politicalÂ thought has been seemed as the doctrine came from Indonesia traditional heritages. These view wasÂ rejected by H.O.S. Tjokroaminoto who argues that socialism has been established and flourished inthe Islamic tradition before it was developed in the West. This article tries to describe H.O.S.Â Tjokroaminotoâs political thought about Islamic socialism which was constructed in the IslamicÂ tradition rooted from Al-Quran and As-Sunnah.